A comprehensive approach to determine the probiotic potential of human-derived Lactobacillus for industrial use - Gregoret, Veronica (2013)
Specific strains should only be regarded as probiotics if they fulfill certain safety, technological and functional criteria. The aim of this work was to study, from a comprehensive point of view (in vitro and in vivo tests), three Lactobacillus strains (L. paracasei JP1, L. rhamnosus 64 and L. gasseri 37) isolated from feces of local newborns, determining some parameters of technological, biological and functional relevance. All strains were able to adequately grow in different economic culture media (cheese whey, buttermilk and milk), which were also suitable as cryoprotectants. As selective media, LP-MRS was more effective than B-MRS for the enumeration of all strains. The strains were resistant to different technological (frozen storage, high salt content) and biological (simulated gastrointestinal digestion after refrigerated storage in acidified milk, bile exposure) challenges. L. rhamnosus 64 and L. gasseri 37, in particular, were sensible to chloramphenicol, erythromycin, streptomycin, tetracycline and vancomycin, increased the phagocytic activity of peritoneal macrophage and induced the proliferation of IgA producing cells in small intestine when administered to mice. Even when clinical trails are still needed, both strains fulfilled the main criteria proposed by FAO/WHO to consider them as potential probiotics for the formulation of new foods.